Does interpersonal self-support matter for freshman nursing students’ professional identity? Evidence from mainland China - Zhang, Ting; Su, Dan; Yang, Yajuan; Li, Shuwen (Frontiers in psychology, 2023)
Many studies have focused on undergraduate nursing students' professional identity (PI), but freshman nursing students (FNSs) have been ignored, and the relationship between interpersonal self-support (ISS) and PI is unknown. This study was designed to determine the patterns of ISS and its association with PI among Chinese FNSs. A cross-sectional survey was conducted among 358 FNSs recruited from two nursing colleges in southeast China. Students completed the Sociodemographic Characteristics Questionnaire, the Interpersonal Self-Support Scale for Adolescent Students, and the Professional Identity Questionnaire for Nurse Students. Latent profile analysis (LPA) was used to determine the patterns of ISS among freshmen. The Bolck-Croon-Hagenaars method was used to examine the influencing role of ISS in PI. LPA indicated that ISS could be classified into three subgroups: the ISS-Individualist group (7.54% of the total sample), ISS-Dependent group (63.13% of the total sample), and ISS-Extrovert group (29.33% of the total sample). Overall, these three profiles differed significantly in the five dimensions of ISS and PI ( < 0.05). The results of pairwise comparisons examined the positive role of the ISS-Extrovert group on the promotion of PI among FNSs. These findings emphasize the need for the promotion of PI and ISS among Chinese FNSs. Freshman students need more confidence and general communication knowledge to maintain harmonious social relationships with others. Parent-teacher association could be applied to nursing education to guide FNSs' positive development of ISS.